The integral of 2- refined rational neutrosophic functions - Iqbal Ahmed Musa; Yaser Ahmad Alhasan (Neutrosophic Sets and Systems)
The main objective of this paper is to study the integral of 2- refined rational neutrosophic functions, by providing direct rules that make it easy for us to find the integral of 2- refined rational neutrosophic functions, where the division of refined neutrosophic number was used to find the integral of 2- refined rational neutrosophic functions. In addition to proving these rules and providing a set of examples that illustrate these ideas.